KESABARAN DAN SYUKUR: JALAN MENUJU TAQWA DALAM PERSPEKTIF SURAH AL-BAQARAH AYAT 152-153 - Ray Alhafiz Munthe; Khairil Alwi Rambe; Taufiq Hidayat Safitra; Edi Hermanto (Tashdiq: Jurnal Kajian Agama dan Dakwah, 2025)
In Surah Al-Baqarah verses 152–153, this paper analyzes the concepts of patience and gratitude as a path to piety. These verses emphasize how important these two qualities are in facing the tests and blessings given by Allah SWT. Verse 152 reminds of God's blessings that always accompany His people, even when they face difficulties, and encourages them to be grateful for all the goodness He has given. Verse 153 then emphasizes the importance of patience in facing various trials in life, emphasizing that Allah SWT always accompanies those who are patient. Based on the interpretation of verses 152–153, this paper analyzes the meaning and role of patience and gratitude in achieving piety. By understanding the meaning of this verse, it is hoped that readers can gain a better understanding of how important these two qualities are for building firm faith and gaining the blessing of Allah SWT. This article was written using a data collection method, where data was obtained by summarizing some information sourced from journals and books.